PENGEMBANGAN PERANGKAT PEMBELAJARAN IPS DENGAN MENGGUNAKAN METODEBRAINSTORMING UNTUK MENINGKATKAN BERPIKIR KRITIS DI KELAS VSEKOLAH DASAR - Suhanadji, Suhirno Muhari (Faculty of Social Science, Universitas Negeri Semarang, 2016)
Research on this developmentwas intended to produce device learning of a syllabus, lesson plans, sheets of students activity, book students, and tests the ability of think critically students on subjects social class grade 5 second semester.The research also aims to know the quality of device learning in terms of implementation learning when learning held. The kind of research this namely research the development of which reference on the model 4D, with stage define, design, development and disseminate.Subject research is the primary school grade 5.Â Research instruments composed of sheets assessment validity syllabus, lesson plans, sheets of students activity, book students, and tests the ability of think critically.Sheets of implementation learning to gauge the quality of the device learning doing by teachers. The results of research device learning to thesyllabus, lesson plans, sheets of student activity, book students, andtests the ability of think critically on grade 5second semester.Based on the results they actually obtained (1) syllabus developed valid with a value of 4.25 criteria perfectly valid(2) lesson plans developed valid with a value of 4,15 criteria perfectly valid(3) sheets of students activity developed valid with a value of 4.4 criteria perfectly valid(4) books students who developed valid with a value of 4,45 criteria perfectly valid(5) tests the ability of think critically developed valid with a value of 4.25 criteria perfectly valid.The results of research activity of device learning with the total the meeting produce the average4.6 with good category once.The results of research tests the ability to think critically students obtained the percentage completion of achievement 92,25% the average value of 78.